Yield and grain dimensions of T. Aman rice varieties as influenced by date of transplanting - Reza, Syeda Nuzhat; Tani, Nahid Nadia; Salim, Muhammad; Hasan, Ahmed Khairul; Akter, Mst Arjina (Asian Journal of Medical and Biological Research, 2016)
A field experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, during June 2013 to December 2013 to study the yield and grain dimensions of transplant aman rice varieties as influenced by date of transplanting. The experimental factors comprised of two factors namely, date of transplanting and variety. Date of transplanting comprised of 18 July, 19 August and 18 September. The variety comprised of Binadhan-7, BRRI dhan57, BR11 and Bashiraj. The experimental field was laid out in a split plot design. Most of the yield parameters were significantly affected by the date of transplanting. The yield and yield contributing characters were highest at 19 August transplanting and lowest at 18 September transplanting. Variety had significant effect on most of the yield and yield contributing characters. BR11 gave the highest grain yield (4.47 t ha-1) and the lowest value was obtained in BRRI dhan57. Among the grain dimensions, Binadhan-7 with 18 July transplanting gave the highest grain length (9.64 mm) whereas BR11 with 18 September transplanting gave the lowest value (7.82mm). Results showed that yield components were highest at 19 August transplanting and after that the reduction occurred at 18 September may be due to low temperature and short day length at flowering stage. Asian J. Med. Biol. Res. September 2016, 2(3): 442-450